2009
DOI: 10.1002/biof.7
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of action of vitamin C in sepsis: Ascorbate modulates redox signaling in endothelium

Abstract: Circulating levels of vitamin C (ascorbate) are low in patients with sepsis. Parenteral administration of ascorbate raises plasma and tissue concentrations of the vitamin and may decrease morbidity. In animal models of sepsis, intravenous ascorbate injection increases survival and protects several microvascular functions, namely, capillary blood flow, microvascular permeability barrier, and arteriolar responsiveness to vasoconstrictors and vasodilators. The effects of parenteral ascorbate on microvascular func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
128
1
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(134 citation statements)
references
References 89 publications
2
128
1
3
Order By: Relevance
“…Plasma AA in patients with multiorgan failure was significantly lower [34], whereas low concentrations were inversely correlated with increased lipid peroxides [69] a marker of increased oxidative stress. Results from animal models demonstrated that AA ameliorates edema and hypotension and improves arteriolar responsiveness and capillary blood flow [70][71][72][73]. Experiments in healthy volunteers after induction of systemic inflammation by low doses of E. coli endotoxemia revealed that the hyporeactivity can be corrected by high doses of vitamin C, suggesting that oxidative stress may represent an important target for inflammation-induced impaired vascular function [74].…”
Section: Vitamin Cmentioning
confidence: 99%
“…Plasma AA in patients with multiorgan failure was significantly lower [34], whereas low concentrations were inversely correlated with increased lipid peroxides [69] a marker of increased oxidative stress. Results from animal models demonstrated that AA ameliorates edema and hypotension and improves arteriolar responsiveness and capillary blood flow [70][71][72][73]. Experiments in healthy volunteers after induction of systemic inflammation by low doses of E. coli endotoxemia revealed that the hyporeactivity can be corrected by high doses of vitamin C, suggesting that oxidative stress may represent an important target for inflammation-induced impaired vascular function [74].…”
Section: Vitamin Cmentioning
confidence: 99%
“…We presume the phenolic compounds included in the fractionated samples from ginkgo-derived CMCs may be responsible for their anti-inflammatory and antioxidative properties (Ríos et al, 2009;Wilson, 2009). Polyphenolic compounds including catechin, quercetin, myricetin, and myricetin-rutinosides are identified as the main components of ethanol extract from many plants (Zhao et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, many reports have reported the efficacy of the water-soluble antioxidant vitamin C for treating sepsis [5,13,[28][29][30][31]. Although copper and zinc, which bind to the superoxide dismutase active center, are essential for maintaining the antioxidant system, these trace elements have not been studied clinically in septic shock patients [27].…”
Section: Discussionmentioning
confidence: 99%